Studi Observasi Proses Pengeritingan Rambut Selang-Seling dalam Praktik Penataan Rambut di Salon - Dhea Vistara S; Grace Daniela; Nusi Wardatun N; Tri Valiza N; Asrah Rezki Fauzani; Mutia Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Hair perming is a hair styling technique aimed at creating waves or curls according to the desired design. The alternating technique is one of the perming methods used to produce a more natural and voluminous hair appearance. This study aims to identify the implementation process, working stages, and final results of hair perming using the alternating technique in salon hair styling practices. The research employed a descriptive observational method by conducting direct observations of the hair perming process on salon clients. Data were collected through observation, documentation, and recording of each working stage during the perming procedure. The observation results indicate that the alternating technique produces more varied curl patterns, a more natural appearance, and evenly distributed hair volume. The success of the perming results is influenced by rod size selection, hair sectioning technique, accuracy of chemical processing time, and the hairstylist’s skills. Therefore, the alternating hair perming technique can be considered an effective alternative method to enhance the aesthetic quality of perming results in salon practices.